The usurer's daughter : male friendship and fictions of women in sixteenth-century England - Hutson, Lorna (Routledge, 1994)
In a brilliant and persuasive series of moves, Lorna Hutson provides startling new readings of Shakespeare, illuminates how social relations were textualized, and focuses on the central importance of the history of the representation of women.